Dietary intake of polycyclic aromatic hydrocarbons (PAHs) from coral reef fish in the Persian Gulf — Human health risk assessment. (1st November 2020) - Ranjbar Jafarabadi, Ali; Mashjoor, Sakineh; Riyahi Bakhtiari, Alireza; Jadot, Catherine
Highlights: PAH-bioaccumulation in reef fish and associated dietary health risks were assessed. Multi-biomarker responses in fish were affected by exposure to PAHs from oil spills. The levels of ∑39 PAHs in Lutjanus argentimaculatus were higher than another species. Consumption of fish by local population could result in increased hazard quotients. Abstract: The present study investigated accumulation of petrogenic polycyclic aromatic hydrocarbons (∑39 PAHs) in the livers and muscles of three coral-reef fish (50 specimens) from the Persian Gulf, Kharg Island (Iran), specifically Lethrinus microdon (n = 18), Lutjanus argentimaculatus (n = 17), and Scomberomorus guttatus (n = 15). For all fish, PAHs originated mostly from petroleum and combustion sources. Concentrations of ∑39 PAHs were 1004 ngg −1 freeze-dried weight (fdw) and 1390 ngg −1 fdw for liver and muscle, respectively. The biota-sediment accumulation factor of 20, 181 and equivalent concentrations of ∑PAHs (liver) were highest for L. argentimaculatus. Most of the abundant PAHs identified were low molecular weight (LMW-PAH) (liver > muscle) with 2–3 aromatic ring. Results for the human health risk assessment concluded the probability of PAHs intake via fish consumption was considerable in this area (lifetime cancer risk (ILCR) > 1 × 10 −5 ; hazard quotients (HQs ) > 1; hazard index (HI) ≈6; the excess cancer risk (ECR) > 1 × 10 −6 ) and, therefore, comprehensive management and long-term monitoring is needed.